An analysis of peer's influence on the learning process and the character building of the children portrayed in the novel A Little Princess by Frances Hodgson Burnett - Indrawati, Shafa Sabila (Passage: Journal of English Language and Literature, 2025)
Peer groups are examples of social interactions, sources where children obtain and receive many things, such as behaviour, attitudes, and interests. This research explores the portrayal of peer influence in a children's literature novel titled A Little Princess (1905) by Frances Hodgson Burnett. By using the qualitative research method, this research aims to investigate how peers can influence children, in this case how the minor characters are influenced by the model main character. The goal of this research is gained by taking the data from analyzing minor characters' behaviour and utterances towards the main character portrayed in the narrative. Bandura's social learning theory (2008) is used to discover the study of peer group influence. In addition, Kenan's characterization theory (2002) is used to determine how the representation is portrayed in the novel. The research shows the minor characters experienced four sub-functions of observational learning: attentional, representational, production, and motivational processes. Moreover, the main character acts as a model example to be observed by the minor characters. Positive and negative impacts related to the learning process and character building are found for students as observers through observational learning processes.